Examples
(1,1,1)(1,1,1) , (0,1,1) , (0,0,1)
Step 1
Assign a name for each vector.
u⃗1=(1,1,1)
u⃗2=(0,1,1)
u⃗3=(0,0,1)
Step 2
The first orthogonal vector is the first vector in the given set of vectors.
v⃗1=u⃗1=(1,1,1)
Step 3
Use the formula to find the other orthogonal vectors.
v⃗k=u⃗k-k-1∑i=1projv⃗i(u⃗k)
Step 4
Step 4.1
Use the formula to find v⃗2.
v⃗2=u⃗2-projv⃗1(u⃗2)
Step 4.2
Substitute (0,1,1) for u⃗2.
v⃗2=(0,1,1)-projv⃗1(u⃗2)
Step 4.3
Find projv⃗1(u⃗2).
Step 4.3.1
Find the dot product.
Step 4.3.1.1
The dot product of two vectors is the sum of the products of the their components.
u⃗2⋅v⃗1=0⋅1+1⋅1+1⋅1
Step 4.3.1.2
Simplify.
Step 4.3.1.2.1
Simplify each term.
Step 4.3.1.2.1.1
Multiply 0 by 1.
u⃗2⋅v⃗1=0+1⋅1+1⋅1
Step 4.3.1.2.1.2
Multiply 1 by 1.
u⃗2⋅v⃗1=0+1+1⋅1
Step 4.3.1.2.1.3
Multiply 1 by 1.
u⃗2⋅v⃗1=0+1+1
u⃗2⋅v⃗1=0+1+1
Step 4.3.1.2.2
Add 0 and 1.
u⃗2⋅v⃗1=1+1
Step 4.3.1.2.3
Add 1 and 1.
u⃗2⋅v⃗1=2
u⃗2⋅v⃗1=2
u⃗2⋅v⃗1=2
Step 4.3.2
Find the norm of v⃗1=(1,1,1).
Step 4.3.2.1
The norm is the square root of the sum of squares of each element in the vector.
||v⃗1||=√12+12+12
Step 4.3.2.2
Simplify.
Step 4.3.2.2.1
One to any power is one.
||v⃗1||=√1+12+12
Step 4.3.2.2.2
One to any power is one.
||v⃗1||=√1+1+12
Step 4.3.2.2.3
One to any power is one.
||v⃗1||=√1+1+1
Step 4.3.2.2.4
Add 1 and 1.
||v⃗1||=√2+1
Step 4.3.2.2.5
Add 2 and 1.
||v⃗1||=√3
||v⃗1||=√3
||v⃗1||=√3
Step 4.3.3
Find the projection of u⃗2 onto v⃗1 using the projection formula.
projv⃗1(u⃗2)=u⃗2⋅v⃗1||v⃗1||2×v⃗1
Step 4.3.4
Substitute 2 for u⃗2⋅v⃗1.
projv⃗1(u⃗2)=2||v⃗1||2×v⃗1
Step 4.3.5
Substitute √3 for ||v⃗1||.
projv⃗1(u⃗2)=2√32×v⃗1
Step 4.3.6
Substitute (1,1,1) for v⃗1.
projv⃗1(u⃗2)=2√32×(1,1,1)
Step 4.3.7
Simplify the right side.
Step 4.3.7.1
Rewrite √32 as 3.
Step 4.3.7.1.1
Use n√ax=axn to rewrite √3 as 312.
projv⃗1(u⃗2)=2(312)2×(1,1,1)
Step 4.3.7.1.2
Apply the power rule and multiply exponents, (am)n=amn.
projv⃗1(u⃗2)=2312⋅2×(1,1,1)
Step 4.3.7.1.3
Combine 12 and 2.
projv⃗1(u⃗2)=2322×(1,1,1)
Step 4.3.7.1.4
Cancel the common factor of 2.
Step 4.3.7.1.4.1
Cancel the common factor.
projv⃗1(u⃗2)=2322×(1,1,1)
Step 4.3.7.1.4.2
Rewrite the expression.
projv⃗1(u⃗2)=231×(1,1,1)
projv⃗1(u⃗2)=231×(1,1,1)
Step 4.3.7.1.5
Evaluate the exponent.
projv⃗1(u⃗2)=23×(1,1,1)
projv⃗1(u⃗2)=23×(1,1,1)
Step 4.3.7.2
Multiply 23 by each element of the matrix.
projv⃗1(u⃗2)=(23⋅1,23⋅1,23⋅1)
Step 4.3.7.3
Simplify each element in the matrix.
Step 4.3.7.3.1
Multiply 23 by 1.
projv⃗1(u⃗2)=(23,23⋅1,23⋅1)
Step 4.3.7.3.2
Multiply 23 by 1.
projv⃗1(u⃗2)=(23,23,23⋅1)
Step 4.3.7.3.3
Multiply 23 by 1.
projv⃗1(u⃗2)=(23,23,23)
projv⃗1(u⃗2)=(23,23,23)
projv⃗1(u⃗2)=(23,23,23)
projv⃗1(u⃗2)=(23,23,23)
Step 4.4
Substitute the projection.
v⃗2=(0,1,1)-(23,23,23)
Step 4.5
Simplify.
Step 4.5.1
Combine each component of the vectors.
(0-(23),1-(23),1-(23))
Step 4.5.2
Subtract 23 from 0.
(-23,1-(23),1-(23))
Step 4.5.3
Write 1 as a fraction with a common denominator.
(-23,33-23,1-(23))
Step 4.5.4
Combine the numerators over the common denominator.
(-23,3-23,1-(23))
Step 4.5.5
Subtract 2 from 3.
(-23,13,1-(23))
Step 4.5.6
Write 1 as a fraction with a common denominator.
(-23,13,33-23)
Step 4.5.7
Combine the numerators over the common denominator.
(-23,13,3-23)
Step 4.5.8
Subtract 2 from 3.
v⃗2=(-23,13,13)
v⃗2=(-23,13,13)
v⃗2=(-23,13,13)
Step 5
Step 5.1
Use the formula to find v⃗3.
v⃗3=u⃗3-projv⃗1(u⃗3)-projv⃗2(u⃗3)
Step 5.2
Substitute (0,0,1) for u⃗3.
v⃗3=(0,0,1)-projv⃗1(u⃗3)-projv⃗2(u⃗3)
Step 5.3
Find projv⃗1(u⃗3).
Step 5.3.1
Find the dot product.
Step 5.3.1.1
The dot product of two vectors is the sum of the products of the their components.
u⃗3⋅v⃗1=0⋅1+0⋅1+1⋅1
Step 5.3.1.2
Simplify.
Step 5.3.1.2.1
Simplify each term.
Step 5.3.1.2.1.1
Multiply 0 by 1.
u⃗3⋅v⃗1=0+0⋅1+1⋅1
Step 5.3.1.2.1.2
Multiply 0 by 1.
u⃗3⋅v⃗1=0+0+1⋅1
Step 5.3.1.2.1.3
Multiply 1 by 1.
u⃗3⋅v⃗1=0+0+1
u⃗3⋅v⃗1=0+0+1
Step 5.3.1.2.2
Add 0 and 0.
u⃗3⋅v⃗1=0+1
Step 5.3.1.2.3
Add 0 and 1.
u⃗3⋅v⃗1=1
u⃗3⋅v⃗1=1
u⃗3⋅v⃗1=1
Step 5.3.2
Find the norm of v⃗1=(1,1,1).
Step 5.3.2.1
The norm is the square root of the sum of squares of each element in the vector.
||v⃗1||=√12+12+12
Step 5.3.2.2
Simplify.
Step 5.3.2.2.1
One to any power is one.
||v⃗1||=√1+12+12
Step 5.3.2.2.2
One to any power is one.
||v⃗1||=√1+1+12
Step 5.3.2.2.3
One to any power is one.
||v⃗1||=√1+1+1
Step 5.3.2.2.4
Add 1 and 1.
||v⃗1||=√2+1
Step 5.3.2.2.5
Add 2 and 1.
||v⃗1||=√3
||v⃗1||=√3
||v⃗1||=√3
Step 5.3.3
Find the projection of u⃗3 onto v⃗1 using the projection formula.
projv⃗1(u⃗3)=u⃗3⋅v⃗1||v⃗1||2×v⃗1
Step 5.3.4
Substitute 1 for u⃗3⋅v⃗1.
projv⃗1(u⃗3)=1||v⃗1||2×v⃗1
Step 5.3.5
Substitute √3 for ||v⃗1||.
projv⃗1(u⃗3)=1√32×v⃗1
Step 5.3.6
Substitute (1,1,1) for v⃗1.
projv⃗1(u⃗3)=1√32×(1,1,1)
Step 5.3.7
Simplify the right side.
Step 5.3.7.1
Rewrite √32 as 3.
Step 5.3.7.1.1
Use n√ax=axn to rewrite √3 as 312.
projv⃗1(u⃗3)=1(312)2×(1,1,1)
Step 5.3.7.1.2
Apply the power rule and multiply exponents, (am)n=amn.
projv⃗1(u⃗3)=1312⋅2×(1,1,1)
Step 5.3.7.1.3
Combine 12 and 2.
projv⃗1(u⃗3)=1322×(1,1,1)
Step 5.3.7.1.4
Cancel the common factor of 2.
Step 5.3.7.1.4.1
Cancel the common factor.
projv⃗1(u⃗3)=1322×(1,1,1)
Step 5.3.7.1.4.2
Rewrite the expression.
projv⃗1(u⃗3)=131×(1,1,1)
projv⃗1(u⃗3)=131×(1,1,1)
Step 5.3.7.1.5
Evaluate the exponent.
projv⃗1(u⃗3)=13×(1,1,1)
projv⃗1(u⃗3)=13×(1,1,1)
Step 5.3.7.2
Multiply 13 by each element of the matrix.
projv⃗1(u⃗3)=(13⋅1,13⋅1,13⋅1)
Step 5.3.7.3
Simplify each element in the matrix.
Step 5.3.7.3.1
Multiply 13 by 1.
projv⃗1(u⃗3)=(13,13⋅1,13⋅1)
Step 5.3.7.3.2
Multiply 13 by 1.
projv⃗1(u⃗3)=(13,13,13⋅1)
Step 5.3.7.3.3
Multiply 13 by 1.
projv⃗1(u⃗3)=(13,13,13)
projv⃗1(u⃗3)=(13,13,13)
projv⃗1(u⃗3)=(13,13,13)
projv⃗1(u⃗3)=(13,13,13)
Step 5.4
Find projv⃗2(u⃗3).
Step 5.4.1
Find the dot product.
Step 5.4.1.1
The dot product of two vectors is the sum of the products of the their components.
u⃗3⋅v⃗2=0(-23)+0(13)+1(13)
Step 5.4.1.2
Simplify.
Step 5.4.1.2.1
Simplify each term.
Step 5.4.1.2.1.1
Multiply 0(-23).
Step 5.4.1.2.1.1.1
Multiply -1 by 0.
u⃗3⋅v⃗2=0(23)+0(13)+1(13)
Step 5.4.1.2.1.1.2
Multiply 0 by 23.
u⃗3⋅v⃗2=0+0(13)+1(13)
u⃗3⋅v⃗2=0+0(13)+1(13)
Step 5.4.1.2.1.2
Multiply 0 by 13.
u⃗3⋅v⃗2=0+0+1(13)
Step 5.4.1.2.1.3
Multiply 13 by 1.
u⃗3⋅v⃗2=0+0+13
u⃗3⋅v⃗2=0+0+13
Step 5.4.1.2.2
Add 0 and 0.
u⃗3⋅v⃗2=0+13
Step 5.4.1.2.3
Add 0 and 13.
u⃗3⋅v⃗2=13
u⃗3⋅v⃗2=13
u⃗3⋅v⃗2=13
Step 5.4.2
Find the norm of v⃗2=(-23,13,13).
Step 5.4.2.1
The norm is the square root of the sum of squares of each element in the vector.
||v⃗2||=√(-23)2+(13)2+(13)2
Step 5.4.2.2
Simplify.
Step 5.4.2.2.1
Use the power rule (ab)n=anbn to distribute the exponent.
Step 5.4.2.2.1.1
Apply the product rule to -23.
||v⃗2||=√(-1)2(23)2+(13)2+(13)2
Step 5.4.2.2.1.2
Apply the product rule to 23.
||v⃗2||=√(-1)22232+(13)2+(13)2
||v⃗2||=√(-1)22232+(13)2+(13)2
Step 5.4.2.2.2
Raise -1 to the power of 2.
||v⃗2||=√12232+(13)2+(13)2
Step 5.4.2.2.3
Multiply 2232 by 1.
||v⃗2||=√2232+(13)2+(13)2
Step 5.4.2.2.4
Raise 2 to the power of 2.
||v⃗2||=√432+(13)2+(13)2
Step 5.4.2.2.5
Raise 3 to the power of 2.
||v⃗2||=√49+(13)2+(13)2
Step 5.4.2.2.6
Apply the product rule to 13.
||v⃗2||=√49+1232+(13)2
Step 5.4.2.2.7
One to any power is one.
||v⃗2||=√49+132+(13)2
Step 5.4.2.2.8
Raise 3 to the power of 2.
||v⃗2||=√49+19+(13)2
Step 5.4.2.2.9
Apply the product rule to 13.
||v⃗2||=√49+19+1232
Step 5.4.2.2.10
One to any power is one.
||v⃗2||=√49+19+132
Step 5.4.2.2.11
Raise 3 to the power of 2.
||v⃗2||=√49+19+19
Step 5.4.2.2.12
Combine the numerators over the common denominator.
||v⃗2||=√4+19+19
Step 5.4.2.2.13
Add 4 and 1.
||v⃗2||=√59+19
Step 5.4.2.2.14
Combine the numerators over the common denominator.
||v⃗2||=√5+19
Step 5.4.2.2.15
Add 5 and 1.
||v⃗2||=√69
Step 5.4.2.2.16
Cancel the common factor of 6 and 9.
Step 5.4.2.2.16.1
Factor 3 out of 6.
||v⃗2||=√3(2)9
Step 5.4.2.2.16.2
Cancel the common factors.
Step 5.4.2.2.16.2.1
Factor 3 out of 9.
||v⃗2||=√3⋅23⋅3
Step 5.4.2.2.16.2.2
Cancel the common factor.
||v⃗2||=√3⋅23⋅3
Step 5.4.2.2.16.2.3
Rewrite the expression.
||v⃗2||=√23
||v⃗2||=√23
||v⃗2||=√23
Step 5.4.2.2.17
Rewrite √23 as √2√3.
||v⃗2||=√2√3
Step 5.4.2.2.18
Multiply √2√3 by √3√3.
||v⃗2||=√2√3⋅√3√3
Step 5.4.2.2.19
Combine and simplify the denominator.
Step 5.4.2.2.19.1
Multiply √2√3 by √3√3.
||v⃗2||=√2√3√3√3
Step 5.4.2.2.19.2
Raise √3 to the power of 1.
||v⃗2||=√2√3√31√3
Step 5.4.2.2.19.3
Raise √3 to the power of 1.
||v⃗2||=√2√3√31√31
Step 5.4.2.2.19.4
Use the power rule aman=am+n to combine exponents.
||v⃗2||=√2√3√31+1
Step 5.4.2.2.19.5
Add 1 and 1.
||v⃗2||=√2√3√32
Step 5.4.2.2.19.6
Rewrite √32 as 3.
Step 5.4.2.2.19.6.1
Use n√ax=axn to rewrite √3 as 312.
||v⃗2||=√2√3(312)2
Step 5.4.2.2.19.6.2
Apply the power rule and multiply exponents, (am)n=amn.
||v⃗2||=√2√3312⋅2
Step 5.4.2.2.19.6.3
Combine 12 and 2.
||v⃗2||=√2√3322
Step 5.4.2.2.19.6.4
Cancel the common factor of 2.
Step 5.4.2.2.19.6.4.1
Cancel the common factor.
||v⃗2||=√2√3322
Step 5.4.2.2.19.6.4.2
Rewrite the expression.
||v⃗2||=√2√331
||v⃗2||=√2√331
Step 5.4.2.2.19.6.5
Evaluate the exponent.
||v⃗2||=√2√33
||v⃗2||=√2√33
||v⃗2||=√2√33
Step 5.4.2.2.20
Simplify the numerator.
Step 5.4.2.2.20.1
Combine using the product rule for radicals.
||v⃗2||=√2⋅33
Step 5.4.2.2.20.2
Multiply 2 by 3.
||v⃗2||=√63
||v⃗2||=√63
||v⃗2||=√63
||v⃗2||=√63
Step 5.4.3
Find the projection of u⃗3 onto v⃗2 using the projection formula.
projv⃗2(u⃗3)=u⃗3⋅v⃗2||v⃗2||2×v⃗2
Step 5.4.4
Substitute 13 for u⃗3⋅v⃗2.
projv⃗2(u⃗3)=13||v⃗2||2×v⃗2
Step 5.4.5
Substitute √63 for ||v⃗2||.
projv⃗2(u⃗3)=13(√63)2×v⃗2
Step 5.4.6
Substitute (-23,13,13) for v⃗2.
projv⃗2(u⃗3)=13(√63)2×(-23,13,13)
Step 5.4.7
Simplify the right side.
Step 5.4.7.1
Simplify the denominator.
Step 5.4.7.1.1
Apply the product rule to √63.
projv⃗2(u⃗3)=13√6232×(-23,13,13)
Step 5.4.7.1.2
Rewrite √62 as 6.
Step 5.4.7.1.2.1
Use n√ax=axn to rewrite √6 as 612.
projv⃗2(u⃗3)=13(612)232×(-23,13,13)
Step 5.4.7.1.2.2
Apply the power rule and multiply exponents, (am)n=amn.
projv⃗2(u⃗3)=13612⋅232×(-23,13,13)
Step 5.4.7.1.2.3
Combine 12 and 2.
projv⃗2(u⃗3)=1362232×(-23,13,13)
Step 5.4.7.1.2.4
Cancel the common factor of 2.
Step 5.4.7.1.2.4.1
Cancel the common factor.
projv⃗2(u⃗3)=1362232×(-23,13,13)
Step 5.4.7.1.2.4.2
Rewrite the expression.
projv⃗2(u⃗3)=136132×(-23,13,13)
projv⃗2(u⃗3)=136132×(-23,13,13)
Step 5.4.7.1.2.5
Evaluate the exponent.
projv⃗2(u⃗3)=13632×(-23,13,13)
projv⃗2(u⃗3)=13632×(-23,13,13)
Step 5.4.7.1.3
Raise 3 to the power of 2.
projv⃗2(u⃗3)=1369×(-23,13,13)
Step 5.4.7.1.4
Cancel the common factor of 6 and 9.
Step 5.4.7.1.4.1
Factor 3 out of 6.
projv⃗2(u⃗3)=133(2)9×(-23,13,13)
Step 5.4.7.1.4.2
Cancel the common factors.
Step 5.4.7.1.4.2.1
Factor 3 out of 9.
projv⃗2(u⃗3)=133⋅23⋅3×(-23,13,13)
Step 5.4.7.1.4.2.2
Cancel the common factor.
projv⃗2(u⃗3)=133⋅23⋅3×(-23,13,13)
Step 5.4.7.1.4.2.3
Rewrite the expression.
projv⃗2(u⃗3)=1323×(-23,13,13)
projv⃗2(u⃗3)=1323×(-23,13,13)
projv⃗2(u⃗3)=1323×(-23,13,13)
projv⃗2(u⃗3)=1323×(-23,13,13)
Step 5.4.7.2
Multiply the numerator by the reciprocal of the denominator.
projv⃗2(u⃗3)=13⋅32×(-23,13,13)
Step 5.4.7.3
Cancel the common factor of 3.
Step 5.4.7.3.1
Cancel the common factor.
projv⃗2(u⃗3)=13⋅32×(-23,13,13)
Step 5.4.7.3.2
Rewrite the expression.
projv⃗2(u⃗3)=12×(-23,13,13)
projv⃗2(u⃗3)=12×(-23,13,13)
Step 5.4.7.4
Multiply 12 by each element of the matrix.
projv⃗2(u⃗3)=(12(-23),12⋅13,12⋅13)
Step 5.4.7.5
Simplify each element in the matrix.
Step 5.4.7.5.1
Cancel the common factor of 2.
Step 5.4.7.5.1.1
Move the leading negative in -23 into the numerator.
projv⃗2(u⃗3)=(12⋅-23,12⋅13,12⋅13)
Step 5.4.7.5.1.2
Factor 2 out of -2.
projv⃗2(u⃗3)=(12⋅2(-1)3,12⋅13,12⋅13)
Step 5.4.7.5.1.3
Cancel the common factor.
projv⃗2(u⃗3)=(12⋅2⋅-13,12⋅13,12⋅13)
Step 5.4.7.5.1.4
Rewrite the expression.
projv⃗2(u⃗3)=(-13,12⋅13,12⋅13)
projv⃗2(u⃗3)=(-13,12⋅13,12⋅13)
Step 5.4.7.5.2
Move the negative in front of the fraction.
projv⃗2(u⃗3)=(-13,12⋅13,12⋅13)
Step 5.4.7.5.3
Multiply 12⋅13.
Step 5.4.7.5.3.1
Multiply 12 by 13.
projv⃗2(u⃗3)=(-13,12⋅3,12⋅13)
Step 5.4.7.5.3.2
Multiply 2 by 3.
projv⃗2(u⃗3)=(-13,16,12⋅13)
projv⃗2(u⃗3)=(-13,16,12⋅13)
Step 5.4.7.5.4
Multiply 12⋅13.
Step 5.4.7.5.4.1
Multiply 12 by 13.
projv⃗2(u⃗3)=(-13,16,12⋅3)
Step 5.4.7.5.4.2
Multiply 2 by 3.
projv⃗2(u⃗3)=(-13,16,16)
projv⃗2(u⃗3)=(-13,16,16)
projv⃗2(u⃗3)=(-13,16,16)
projv⃗2(u⃗3)=(-13,16,16)
projv⃗2(u⃗3)=(-13,16,16)
Step 5.5
Substitute the projections.
v⃗3=(0,0,1)-(13,13,13)-(-13,16,16)
Step 5.6
Simplify.
Step 5.6.1
Combine each component of the vectors.
(0-(13),0-(13),1-(13))-(-13,16,16)
Step 5.6.2
Combine each component of the vectors.
(0-(13)-(-13),0-(13)-(16),1-(13)-(16))
Step 5.6.3
Multiply -(-13).
Step 5.6.3.1
Multiply -1 by -1.
(0-13+1(13),0-(13)-(16),1-(13)-(16))
Step 5.6.3.2
Multiply 13 by 1.
(0-13+13,0-(13)-(16),1-(13)-(16))
(0-13+13,0-(13)-(16),1-(13)-(16))
Step 5.6.4
Combine fractions.
Step 5.6.4.1
Combine the numerators over the common denominator.
(-1+13,0-(13)-(16),1-(13)-(16))
Step 5.6.4.2
Simplify the expression.
Step 5.6.4.2.1
Add -1 and 1.
(03,0-(13)-(16),1-(13)-(16))
Step 5.6.4.2.2
Divide 0 by 3.
(0,0-(13)-(16),1-(13)-(16))
(0,0-(13)-(16),1-(13)-(16))
(0,0-(13)-(16),1-(13)-(16))
Step 5.6.5
Multiply -1 by 16.
(0,0-13-16,1-(13)-(16))
Step 5.6.6
Subtract 13 from 0.
(0,-13-16,1-(13)-(16))
Step 5.6.7
To write -13 as a fraction with a common denominator, multiply by 22.
(0,-13⋅22-16,1-(13)-(16))
Step 5.6.8
Write each expression with a common denominator of 6, by multiplying each by an appropriate factor of 1.
Step 5.6.8.1
Multiply 13 by 22.
(0,-23⋅2-16,1-(13)-(16))
Step 5.6.8.2
Multiply 3 by 2.
(0,-26-16,1-(13)-(16))
(0,-26-16,1-(13)-(16))
Step 5.6.9
Simplify the expression.
Step 5.6.9.1
Combine the numerators over the common denominator.
(0,-2-16,1-(13)-(16))
Step 5.6.9.2
Subtract 1 from -2.
(0,-36,1-(13)-(16))
(0,-36,1-(13)-(16))
Step 5.6.10
Cancel the common factor of -3 and 6.
Step 5.6.10.1
Factor 3 out of -3.
(0,3(-1)6,1-(13)-(16))
Step 5.6.10.2
Cancel the common factors.
Step 5.6.10.2.1
Factor 3 out of 6.
(0,3⋅-13⋅2,1-(13)-(16))
Step 5.6.10.2.2
Cancel the common factor.
(0,3⋅-13⋅2,1-(13)-(16))
Step 5.6.10.2.3
Rewrite the expression.
(0,-12,1-(13)-(16))
(0,-12,1-(13)-(16))
(0,-12,1-(13)-(16))
Step 5.6.11
Move the negative in front of the fraction.
(0,-12,1-(13)-(16))
Step 5.6.12
Find the common denominator.
Step 5.6.12.1
Write 1 as a fraction with denominator 1.
(0,-12,11-(13)-(16))
Step 5.6.12.2
Multiply 11 by 66.
(0,-12,11⋅66-(13)-(16))
Step 5.6.12.3
Multiply 11 by 66.
(0,-12,66-(13)-(16))
Step 5.6.12.4
Multiply 13 by 22.
(0,-12,66-(13⋅22)-(16))
Step 5.6.12.5
Multiply 13 by 22.
(0,-12,66-23⋅2-(16))
Step 5.6.12.6
Reorder the factors of 3⋅2.
(0,-12,66-22⋅3-(16))
Step 5.6.12.7
Multiply 2 by 3.
(0,-12,66-26-(16))
(0,-12,66-26-(16))
Step 5.6.13
Combine the numerators over the common denominator.
(0,-12,6-2-16)
Step 5.6.14
Simplify by subtracting numbers.
Step 5.6.14.1
Subtract 2 from 6.
(0,-12,4-16)
Step 5.6.14.2
Subtract 1 from 4.
(0,-12,36)
(0,-12,36)
Step 5.6.15
Cancel the common factor of 3 and 6.
Step 5.6.15.1
Factor 3 out of 3.
(0,-12,3(1)6)
Step 5.6.15.2
Cancel the common factors.
Step 5.6.15.2.1
Factor 3 out of 6.
(0,-12,3⋅13⋅2)
Step 5.6.15.2.2
Cancel the common factor.
(0,-12,3⋅13⋅2)
Step 5.6.15.2.3
Rewrite the expression.
v⃗3=(0,-12,12)
v⃗3=(0,-12,12)
v⃗3=(0,-12,12)
v⃗3=(0,-12,12)
v⃗3=(0,-12,12)
Step 6
Find the orthonormal basis by dividing each orthogonal vector by its norm.
Span{v⃗1||v⃗1||,v⃗2||v⃗2||,v⃗3||v⃗3||}
Step 7
Step 7.1
To find a unit vector in the same direction as a vector v⃗, divide by the norm of v⃗.
v⃗|v⃗|
Step 7.2
The norm is the square root of the sum of squares of each element in the vector.
√12+12+12
Step 7.3
Simplify.
Step 7.3.1
One to any power is one.
√1+12+12
Step 7.3.2
One to any power is one.
√1+1+12
Step 7.3.3
One to any power is one.
√1+1+1
Step 7.3.4
Add 1 and 1.
√2+1
Step 7.3.5
Add 2 and 1.
√3
√3
Step 7.4
Divide the vector by its norm.
(1,1,1)√3
Step 7.5
Divide each element in the vector by √3.
(1√3,1√3,1√3)
(1√3,1√3,1√3)
Step 8
Step 8.1
To find a unit vector in the same direction as a vector v⃗, divide by the norm of v⃗.
v⃗|v⃗|
Step 8.2
The norm is the square root of the sum of squares of each element in the vector.
√(-23)2+(13)2+(13)2
Step 8.3
Simplify.
Step 8.3.1
Use the power rule (ab)n=anbn to distribute the exponent.
Step 8.3.1.1
Apply the product rule to -23.
√(-1)2(23)2+(13)2+(13)2
Step 8.3.1.2
Apply the product rule to 23.
√(-1)22232+(13)2+(13)2
√(-1)22232+(13)2+(13)2
Step 8.3.2
Raise -1 to the power of 2.
√12232+(13)2+(13)2
Step 8.3.3
Multiply 2232 by 1.
√2232+(13)2+(13)2
Step 8.3.4
Raise 2 to the power of 2.
√432+(13)2+(13)2
Step 8.3.5
Raise 3 to the power of 2.
√49+(13)2+(13)2
Step 8.3.6
Apply the product rule to 13.
√49+1232+(13)2
Step 8.3.7
One to any power is one.
√49+132+(13)2
Step 8.3.8
Raise 3 to the power of 2.
√49+19+(13)2
Step 8.3.9
Apply the product rule to 13.
√49+19+1232
Step 8.3.10
One to any power is one.
√49+19+132
Step 8.3.11
Raise 3 to the power of 2.
√49+19+19
Step 8.3.12
Combine the numerators over the common denominator.
√4+19+19
Step 8.3.13
Add 4 and 1.
√59+19
Step 8.3.14
Combine the numerators over the common denominator.
√5+19
Step 8.3.15
Add 5 and 1.
√69
Step 8.3.16
Cancel the common factor of 6 and 9.
Step 8.3.16.1
Factor 3 out of 6.
√3(2)9
Step 8.3.16.2
Cancel the common factors.
Step 8.3.16.2.1
Factor 3 out of 9.
√3⋅23⋅3
Step 8.3.16.2.2
Cancel the common factor.
√3⋅23⋅3
Step 8.3.16.2.3
Rewrite the expression.
√23
√23
√23
Step 8.3.17
Rewrite √23 as √2√3.
√2√3
√2√3
Step 8.4
Divide the vector by its norm.
(-23,13,13)√2√3
Step 8.5
Divide each element in the vector by √2√3.
(-23√2√3,13√2√3,13√2√3)
Step 8.6
Simplify.
Step 8.6.1
Multiply the numerator by the reciprocal of the denominator.
(-23⋅√3√2,13√2√3,13√2√3)
Step 8.6.2
Multiply √3√2 by 23.
(-√3⋅2√2⋅3,13√2√3,13√2√3)
Step 8.6.3
Move 2 to the left of √3.
(-2√3√2⋅3,13√2√3,13√2√3)
Step 8.6.4
Move 3 to the left of √2.
(-2√33√2,13√2√3,13√2√3)
Step 8.6.5
Multiply the numerator by the reciprocal of the denominator.
(-2√33√2,13⋅√3√2,13√2√3)
Step 8.6.6
Multiply 13 by √3√2.
(-2√33√2,√33√2,13√2√3)
Step 8.6.7
Multiply the numerator by the reciprocal of the denominator.
(-2√33√2,√33√2,13⋅√3√2)
Step 8.6.8
Multiply 13 by √3√2.
(-2√33√2,√33√2,√33√2)
(-2√33√2,√33√2,√33√2)
(-2√33√2,√33√2,√33√2)
Step 9
Step 9.1
To find a unit vector in the same direction as a vector v⃗, divide by the norm of v⃗.
v⃗|v⃗|
Step 9.2
The norm is the square root of the sum of squares of each element in the vector.
√02+(-12)2+(12)2
Step 9.3
Simplify.
Step 9.3.1
Raising 0 to any positive power yields 0.
√0+(-12)2+(12)2
Step 9.3.2
Use the power rule (ab)n=anbn to distribute the exponent.
Step 9.3.2.1
Apply the product rule to -12.
√0+(-1)2(12)2+(12)2
Step 9.3.2.2
Apply the product rule to 12.
√0+(-1)21222+(12)2
√0+(-1)21222+(12)2
Step 9.3.3
Raise -1 to the power of 2.
√0+11222+(12)2
Step 9.3.4
Multiply 1222 by 1.
√0+1222+(12)2
Step 9.3.5
One to any power is one.
√0+122+(12)2
Step 9.3.6
Raise 2 to the power of 2.
√0+14+(12)2
Step 9.3.7
Apply the product rule to 12.
√0+14+1222
Step 9.3.8
One to any power is one.
√0+14+122
Step 9.3.9
Raise 2 to the power of 2.
√0+14+14
Step 9.3.10
Add 0 and 14.
√14+14
Step 9.3.11
Combine the numerators over the common denominator.
√1+14
Step 9.3.12
Add 1 and 1.
√24
Step 9.3.13
Cancel the common factor of 2 and 4.
Step 9.3.13.1
Factor 2 out of 2.
√2(1)4
Step 9.3.13.2
Cancel the common factors.
Step 9.3.13.2.1
Factor 2 out of 4.
√2⋅12⋅2
Step 9.3.13.2.2
Cancel the common factor.
√2⋅12⋅2
Step 9.3.13.2.3
Rewrite the expression.
√12
√12
√12
Step 9.3.14
Rewrite √12 as √1√2.
√1√2
Step 9.3.15
Any root of 1 is 1.
1√2
1√2
Step 9.4
Divide the vector by its norm.
(0,-12,12)1√2
Step 9.5
Divide each element in the vector by 1√2.
(01√2,-121√2,121√2)
Step 9.6
Simplify.
Step 9.6.1
Multiply the numerator by the reciprocal of the denominator.
(0√2,-121√2,121√2)
Step 9.6.2
Multiply 0 by √2.
(0,-121√2,121√2)
Step 9.6.3
Multiply the numerator by the reciprocal of the denominator.
(0,-12√2,121√2)
Step 9.6.4
Combine √2 and 12.
(0,-√22,121√2)
Step 9.6.5
Multiply the numerator by the reciprocal of the denominator.
(0,-√22,12√2)
Step 9.6.6
Combine 12 and √2.
(0,-√22,√22)
(0,-√22,√22)
(0,-√22,√22)
Step 10
Substitute the known values.
Span{(1√3,1√3,1√3),(-2√33√2,√33√2,√33√2),(0,-√22,√22)}